Ecumenical cooperation in the field of catechesis, religious education, and universities as well as communicatio in sacris according to the Ecumenical Directory = La coopération oecuménique dans la catéchèse, l’enseignement religieux et les écoles supérieures ainsi que Communication in Sacris selon le Directoire oecuménique = La collaborazione ecumenica nel campo della catechesi, dell’istruzione religiosa e delle università nonché la Communicatio in Sacris secondo il Direttorio ecumenico - Rees, Wilhelm (Ecumeny and law, 2018)
The five-hundredth anniversary of the Reformation falling in 2017 has raised awareness for the ecumenical movement and emphasized common efforts and convergences, but it has made us aware of the lasting division between the Christian denominations. At first, the essay illuminates approaches to ecumenism of the Roman Catholic Church. As faith manifests itself not only in announcement and teaching, but also in Christian doing and acting as well in liturgical celebration, the article also presents on the basis of the Ecumenical Directory and other relevant texts ecumenical formation and cooperation in the field of catechesis, religious education and universities and spiritual activity among the baptized. Finally, there will be suggestions for future ecumenical development and cooperation in these areas.